THE EFFECT OF ORGANIZATIONAL CULTURE ON EMPLOYEE JOB SATISFACTION IN 5-STAR HOTELS IN CAPPADOCIA - Uçak, Hatice (International Scientific Journal Vision, 2025)
Tourism businesses are one of the sectors where employee satisfaction and motivation play a critical role with their service-oriented structure. Job satisfaction of employees in these hotel businesses directly affects service quality and customer satisfaction. In this context, hotels in the tourism sector have to create change and motivate the manpower to create change in order to achieve competitive advantage and survive in the long term. Organizational culture in businesses; the attitudes, behaviors, production style and social relations developed by managers within the organization stand out as a determining factor on employees’ job satisfaction. The aim of this research is to reveal the effect of organizational culture on job satisfaction in 5-star hotel enterprises operating in Nevşehir province and its districts. According to the results of the research, it was determined that participation, consistency and harmony dimensions of organizational culture have a positive and significant effect on job satisfaction, while the vision dimension of organizational culture does not have a significant effect on job satisfaction.